BIG DATA ANALYTICS IN THE CONTEXT OF BUSINESS ENTERPRISES - BABUCEA ANA-GABRIELA; RĂBONȚU CECILIA-IRINA (Analele Universităţii Constantin Brâncuşi din Târgu Jiu : Seria Economie, 2022)
In the context of the new digital economy, in a visible process accelerated by the Covid-19 pandemic, more and more organizations, especially those that want to make a profit, business enterprises, choose to digital transform by using big data, cloud computing, and artificial intelligence, technologies which offer both unsuspected opportunities and risks. According to the European Commission's 2030 Digital Compass: The European Road to the Digital Decade, published on March 9, 2021, the digital transformation of business in the EU Member States by 2030 targets the use of cloud computing, artificial intelligence, and big data in 75% of total EU companies and at least a basic level of digital intensity for 90% of small and medium-sized enterprises (SMEs). In this regard, this paper aims to, in addition to conceptualizing Big data analytics and related terms in the context of enterprises, to take a picture of the current state of usage by enterprises of big data analysis through machine learning, natural language processing, natural language or speech recognition in conjunction with key factors such as the acquisition of cloud computing services and employees' ability to use computers with access to the World Wide Web. The statistical data used come from the Eurostat database and the DESI 2022 Report.